MEDIATION AS A METHOD OF PRE-TRIAL SETTLEMENT OF PUBLIC LEGAL DISPUTES IN THE FIELD OF STATE REGISTRATION - Olena S. Lunina; Volodymyr Yu. Poplavskyi (Alfred Nobel University Journal of Law)
The article is devoted to the study of such a method of pre-trial settlement of public legal disputes in the field of state registration as mediation. It is emphasized that the creation of opportunities for the development of alternative (non-judicial) methods of dispute resolution is one of the main tasks of a democratic, legal state, which tries to ensure the protection and guarantee of the rights of all subjects of law at the appropriate level. This creates an obligation for the state to promote the development of such non-state institutions, such as, in particular, intermediaries (mediators), who help to settle the dispute without bringing it to court. It has been determined that mediation is the activity of professional intermediaries who direct participants of legal dispute into compromise and settlement of the dispute independently by the participants. The article considers peculiarities of mediation procedure in administrative court. Existing additional difficulties in administrative proceedings for the mediation procedure were considered. The content of the draft law of Ukraine «On mediation» concerning such complications has been analyzed. The existing division of the mediation procedure at this stage was examined. It has been observed that the practice of settling conflicts between authorities and private individuals in pre-trial proceedings tends to indicate a reluctance on the part of the authorities to compromise, not only because of the legal nature of their decisions, but also because of certain, so to say, established business practices for quite some time. This is a fundamental reluctance of the authorities to compromise. It is indicated the legislative and factual prerequisites for the application of the mediation agreement in the settlement of public law disputes in the field of state registration, which combines the advantages of both the mediation procedure (economy in terms of time and money, significant relief of the judicial system) and the trial procedure (application guarantees of subjective rights, freedoms, legitimate interests at the level of administration of justice). The author has submitted proposals on improvement of administrative legislation aimed at settlement of mediation as a way of pre-trial settlement of public-legal disputes in the sphere of state registration.